Estimate Outcome Value of Doubling Cell Growth Using Fuzzy Regression Method - Ahmad, W. M. A. W.; Rohim, R. A. A.; Ismail, N. H. (Engineering, Technology & Applied Science Research, 2019)
In this paper, the fundamental concepts used in different disciplines are described and these concepts are written into one common theme: assessing crossness agreement of observation. Focus was given on continuous measurements and methodological approaches for expressing these methods mathematically, both for cases with and without reference. The build method was tested and applied to biological sciences data. The objective of the study was to determine the agreement between the two methods on microorganism data sets in order to determine if they can be used interchangeably and to estimate the fuzzy and bootstrap parameters of the models. The value of interclass correlation (ICC) by using a linear equation is 0.79661 (substantial agreement) and the value of ICC using fuzzy regression equation is 0.82692 (almost perfect agreement).